Lean human resources : redesigning HR processes for a culture of continuous improvement - Jekiel, Cheryl M. (New York, NY : Routledge/Productivity Press, 2020)
"Encouraging a long overdue shift in thinking, this second edition of this groundbreaking book provides managers and executives with the means to maximize employee potential by first showing them how to increase the improvement power of their HR departments. Cheryl M. Jekiel, who has been implementing Lean initiatives out of HR offices for more than 20 years, defines the people-related approaches and practices needed to alter any cultural dynamic that keeps employees from leveraging their peak abilities. She looks at why so many companies allow this sort of waste to exist, how traditional HR departments have not been especially effective in combating waste, and why current HR departments should be seen differently -- as a partner delivering exceptional customer service to employees. This second edition reflects on the material from presented in the first edition, how it has affected Lean HR environments, and how it has changed to accommodate new challenges and practices. It is not only for experts on Continuous Improvement or Lean Implementations, but for readers who are looking to strengthen their HR department and optimize employees' abilities in the workplace"--
OCLC-licensed vendor bibliographic record.
Keywords: Personnel management; Quality control -- Management; Organizational effectiveness; BUSINESS & ECONOMICS / Human Resources & Personnel Management; BUSINESS & ECONOMICS / Quality Control; BUSINESS & ECONOMICS / Workplace Culture; Lean management